Lope de Vega como escritor cortesano La Filomena (1621) y "La Circe" (1624) a estudio - LÓPEZ LORENZO, CIPRIANO (Clásicos Hispánicos, 2023)
Lope de Vega's lyrical career has been studied through different authorial masks that the poet adopts according to times and interests. Showing off the nickname by which he was known in life, the Phoenix reinvents himself and succeeds himself: poet of ballads, poet of Petrarchan songbooks, sacred, courtier, and even burlesque. Of all of them, the courtly or cultured Lope has not received the attention it deserves, since not even the masterpieces of that period have received updated critical editions. We are speaking, then, of a poet who, after the accession to the throne of Felipe IV, puts a pike in the publishing market with two works of difficult generic taxonomy: La Filomena (1621) and La Circe (1624). With them, Lope delves into literary subgenres little traveled by him, such as the Cervantine-style short novel. But what motivates such an authorial turn in the twenties? What is Lope pursuing with these two peculiar volumes and what strategies does he use to build this renewed self? This study addresses all these questions, and others of greater depth, whose hypotheses are ultimately intended to outline a clearer profile of the author in his full maturity